Upaya Menggugah Kepedulian Sosial Mahasiswa terhadap Masyarakat Miskin di Desa Pasirjaya Kecamatan Cilamaya Kulon Karawang - Medi Nopiana; Muhamad Alief Alfarizki; Hananta Permana Akbar Satriatama; Muhammad Adli Naufal (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
The community service team feels concerned about the decreasing social awareness among the younger generation toward the conditions of the surrounding community. It encouraged the community service team to carry out this community service activity. The community service team makes efforts to inspire students of Universitas Singaperbangsa Karawang to care more about the lives of remote communities in Karawang Regency, particularly the community of Tanjungbaru Hutment, Pasirjaya Village, Cilamaya Kulon Subdistrict. The selection of this location was based on previous observations by the community service team, which indicated that nearly all the people in the village remained poor. The community service team applied the observational socialization method in implementing the activity. The results of this activity provided benefits for the students, including gaining insight into the importance of social awareness for the poor, especially in coastal and remote areas in Karawang Regency. In addition, this activity strengthened students' understanding of the Macroeconomic Theory course material, particularly regarding the importance of equitable development in efforts to overcome poverty in a specific area.